Pengaruh Perceived Organizational Support dan Kreativitas terhadap Komitmen Organisasi dengan Mediasi Motivasi Kerja pada UKM Kuliner di Kota Bogor - Elizabeth, Roosganda; Notosudjono, Didik; Hamzah, Hamzah; Yusnita, Nancy; Moeins, Anoesyirwan (Universitas Galuh, 2025)
This study aims to analyze the influence of Perceived Organizational Support (POS) and Creativity on Organizational Commitment (OC), with Work Motivation as a mediating variable, among employees of small and medium culinary enterprises (SMEs) in Bogor City, Indonesia. The culinary SME sector faces challenges such as high employee turnover and low organizational loyalty, which potentially threaten business sustainability. Using a quantitative approach, data were collected through a structured questionnaire distributed to 230 respondents actively working in culinary SMEs. The study employed Structural Equation Modeling (SEM) to examine the relationships among the variables. The findings reveal that POS has a significant effect on both Work Motivation and Organizational Commitment, while Creativity significantly influences Work Motivation, but does not have a direct significant effect on Organizational Commitment. Work Motivation is found to mediate the relationships between both POS and Creativity on Organizational Commitment. These results emphasize the critical role of organizational support and employee intrinsic drive-in enhancing employee loyalty and supporting business sustainability in SMEs. This study provides theoretical contributions to organizational behavior models in informal sectors and practical implications for human resource management strategies in Indonesian culinary SMEs.